ANALISIS KEMAMPUAN INTERPRETASI GRAFIK MAHASISWA PADA MATERI GERAK LURUS - Fita Fatimah (STKIP PGRI Situbondo, 2023)
Graphs are a form of presenting data that shows relationships or comparisons between variables as well as patterns and tendencies of a data. The ability to interpret graphs is needed so that we can get the right information from the data presented. In basic physics courses, a lot of data is presented in graphical form, one of which is in the material of straight motion. This research is a quantitative descriptive study that aims to determine students' abilities in interpreting graphs on straight motion material in basic physics courses. The instrument used was in the form of multiple choice questions which were tested on 26 students participating in basic physics courses. Based on the data analysis carried out, the result was that students' interpretation abilities in general were still low where on average students were only able to solve graph interpretation questions by 21.8% and only 7.7% of students were able to complete graph interpretation questions up to 50%.